2018
DOI: 10.1038/s41467-018-03017-1
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of TAD boundaries reveals preferential insulation of super-enhancers by strong boundaries

Abstract: The metazoan genome is compartmentalized in areas of highly interacting chromatin known as topologically associating domains (TADs). TADs are demarcated by boundaries mostly conserved across cell types and even across species. However, a genome-wide characterization of TAD boundary strength in mammals is still lacking. In this study, we first use fused two-dimensional lasso as a machine learning method to improve Hi-C contact matrix reproducibility, and, subsequently, we categorize TAD boundaries based on thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 49 publications
10
137
2
Order By: Relevance
“…2c). This is consistent with recent studies showing that super-enhancers are enriched with CTCF more frequently than typical enhancers 39,40 .…”
Section: Changes In H3k27ac Are Associated With Changes In Gene Regulsupporting
confidence: 93%
“…2c). This is consistent with recent studies showing that super-enhancers are enriched with CTCF more frequently than typical enhancers 39,40 .…”
Section: Changes In H3k27ac Are Associated With Changes In Gene Regulsupporting
confidence: 93%
“…To assess whether TADs are affected after IR, we identified TAD boundaries and calculated the boundary strength (degree of spatial separation between TADs) for each boundary using both the InsulationScore 36 and the Hicratio method 37 . Both methods determined that TAD boundary strength increases in both BJ-5ta and GM12878 cells 24 hours after IR ( Fig.…”
Section: Tad Boundary Strength and Ctcf Loops Increase After Exposurementioning
confidence: 99%
“…Topologically associating domains (TADs) boundaries were called on 40 kb binned matrices using two methods: the InsulationScore method, as detailed in Crane et al 36 , available as matrix2insulation in the cworld-dekker github package, and the Hicratio method, as described in Gong et al 37 . For the InsulationScore, a 500 kb insulation square size was used, and for the Hicratio method, we used d = 400 kb.…”
Section: Tad Calling Insulation Contact Maps and Tad Boundary Scorementioning
confidence: 99%
“…We identified from ≈ 5,400 (chicken) to 11,000 (pig) TADs of variable sizes (150 to 220Kb on average, Table S15 and supplementary data file 12), with a 90-92% genome-wide coverage. To validate these domains predicted by armatus [43] (see Methods), we computed three metrics along the genome: the Directionality Index (DI), to quantify the degree of upstream or downstream interaction bias for any genomic region [44], the local interaction score to represent the insulation profile along the genome [45,46], and the density of in silico predicted CTCF binding sites, expected to be prevalent at TAD boundaries [47,48]. For each species, we observed that the distribution of these three metrics was consistent with previous reports on model organisms (Figure 7 and Figure S26), supporting the relevance of our topological annotation.…”
Section: Comprehensive Maps Of Topological Domains and Genomic Comparmentioning
confidence: 99%
“…To estimate the structural impact of each TAD boundary, we used the local interaction score as used by [45] and [46] and sometimes referred to as "interaction ratio" or "insulation profile". Within a sliding window of 500kb along the genome (step=10Kb), the insulation score ratio is defined as the proportion of read pairs that span across the middle of the window.…”
Section: Chromatin Structure Conservation Across Speciesmentioning
confidence: 99%